ANALISIS KINERJA KEUANGAN PT. INDORIS PRINTINGDO BERSUMBER PADA KEPUTUSAN MENTERI BUMN NOMOR: KEP-100/MBU/2002 - Wardokhi Wardokhi (Universitas Pamulang, 2018)
ABSTRACT This reseaarch aims to determine the financial performance of PT. Indoris Printingdo, based on the Decree of the Minister of BUMN no. 100 / MBU / 2002 on Rating of State-Owned Enterprise Health Level during the period of 2013 - 2015. Data collection methods in this study is obtained by quoting directly from the financial statements in PT. Indoris Printingdo from 2013 to 2015. The analysis technique in this research is quantitative descriptive analysis. The data analysis used is based on the Decree of the Minister of BUMN no:100 / MBU / 2002.Based on the results of research known that the financial performance of PT. Indoris Printingdo based on Decree of the Minister of BUMN no.100 / MBU / 2002 is in 2013 to get the title of